Cork Oak Vulnerability to Fire: The Role of Bark Harvesting, Tree Characteristics and Abiotic Factors - Catry, Filipe X; Moreira, Francisco; Pausas, Juli G; Fernandes, Paulo M; Rego, Francisco; Cardillo, Enrique; Curt, Thomas (PLoS ONE, 2012)
Forest ecosystems where periodical tree bark harvesting is a major economic activity may be particularly vulnerable to disturbances such as fire, since debarking usually reduces tree vigour and protection against external agents. In this paper we asked how cork oak Quercus suber trees respond after wildfires and, in particular, how bark harvesting affects post-fire tree survival and resprouting. We gathered data from 22 wildfires (4585 trees) that occurred in three southern European countries (Portugal, Spain and France), covering a wide range of conditions characteristic of Q. suber ecosystems. Post-fire tree responses (tree mortality, stem mortality and crown resprouting) were examined in relation to management and ecological factors using generalized linear mixed-effects models. Results showed that bark thickness and bark harvesting are major factors affecting resistance of Q. suber to fire. Fire vulnerability was higher for trees with thin bark (young or recently debarked individuals) and decreased with increasing bark thickness until cork was 3–4 cm thick. This bark thickness corresponds to the moment when exploited trees are debarked again, meaning that exploited trees are vulnerable to fire during a longer period. Exploited trees were also more likely to be top-killed than unexploited trees, even for the same bark thickness. Additionally, vulnerability to fire increased with burn severity and with tree diameter, and was higher in trees burned in early summer or located in drier south-facing aspects. We provided tree response models useful to help estimating the impact of fire and to support management decisions. The results suggested that an appropriate management of surface fuels and changes in the bark harvesting regime (e.g. debarking coexisting trees in different years or increasing the harvesting cycle) would decrease vulnerability to fire and contribute to the conservation of cork oak ecosystems.
Keywords: bark tickness; cork harvesting; Cork oak; fire; fire vulnerability; management (voyant); mortality; post-fire response

Factors affecting post-fire crown regeneration in cork oak (Quercus suber L.) trees - Catry, Filipe Xavier; Moreira, Francisco; Duarte, Inês; Acácio, Vanda (European Journal of Forest Research, 2009)
Cork oak (Quercus suber) forests are acknowledged for their biodiversity and economic (mainly cork production) values. WildWres are one of the main threats contributing to cork oak decline in the Mediterranean Basin, and one major question that managers face after Wre in cork oak stands is whether the burned trees should be coppiced or not. This decision can be based on the degree of expected crown regeneration assessed immediately after Wre. In this study we carried out a post-Wre assessment of the degree of crown recovery in 858 trees being exploited for cork production in southern Portugal, 1.5 years after a wildWre. Using logistic regression, we modelled good or poor crown recovery probability as a function of tree and stand variables. The main variables inXuencing the likelihood of good or poor crown regeneration were bark thickness, charring height, aspect and tree diameter. We also developed management models, including simpler but easier to measure variables, which had a lower predictive power but can be used to help managers to identify, immediately after Wre, trees that will likely show good crown regeneration, and trees that will likely die or show poor regeneration (and thus, potential candidates for trunk coppicing).
Keywords: Cork oak; crown regeneration; Forest management; wild w res; wildfires

Factors affecting post-fire crown regeneration in cork oak (Quercus suber L.) trees - Catry, Filipe Xavier; Moreira, Francisco; Duarte, Inês; Acácio, Vanda (European Journal of Forest Research, 2009)
Cork oak (Quercus suber) forests are acknowledged for their biodiversity and economic (mainly cork production) values. WildWres are one of the main threats contributing to cork oak decline in the Mediterranean Basin, and one major question that managers face after Wre in cork oak stands is whether the burned trees should be coppiced or not. This decision can be based on the degree of expected crown regeneration assessed immediately after Wre. In this study we carried out a post-Wre assessment of the degree of crown recovery in 858 trees being exploited for cork production in southern Portugal, 1.5 years after a wildWre. Using logistic regression, we modelled good or poor crown recovery probability as a function of tree and stand variables. The main variables inXuencing the likelihood of good or poor crown regeneration were bark thickness, charring height, aspect and tree diameter. We also developed management models, including simpler but easier to measure variables, which had a lower predictive power but can be used to help managers to identify, immediately after Wre, trees that will likely show good crown regeneration, and trees that will likely die or show poor regeneration (and thus, potential candidates for trunk coppicing).
Keywords: Cork oak; crown regeneration; Forest management; wild w res; wildfires